Composição fitoquímica e atividade biológica do extrato bruto e frações da Equisetum hyemale - Alves, Camilla Filippi dos Santos (2015)
The use of plants for medicinal purposes is an ancient practice because vegetables have in its composition chemical structures with important pharmacological activities. In this study we highlight the hyemale Equisetum species, belonging to the phylum Sphenophyta and Equisetaceae family. This is an aerial plant, commonly found in tropical and temperate climates. The infusion of plant stems is popularly used as diuretic, antihypertensive and for the treatment of infectious diseases and inflammations. All species of the genus are known as Horsetail. This study aimed to carry out a phytochemical study and evaluate the antioxidant activity, antimicrobial, and anti-parasitic antibiofilm the crude extract and fractions of E. hyemale. The plant was collected in the municipality of Santa Maria, district of São Martinho da Serra, in November 2013. The voucher specimen of the material was deposited in the Herbarium UFSM Forestry, cataloged under the registration number 6756. The material was macerated with ethanol (70%) and filtered to afford a portion of the aqueous extract was reserved for obtaining the crude extract and ethanol extract was evaporated. The remainder was partitioned into separate vials using increasingly polar solvents: dichloromethane, ethyl acetate and butanol, and the crude extract was obtained by drying the aqueous extract. Assays of flavonoids and polyphenols totas through the colorimetric quantification technique were performed. To determine the antioxidant capacity was used DPPH technique. The phenolic acids were identified and quantified by HPLC-DAD. The antimicrobial activity was evaluated by broth microdilution technique and the reductive capacity of biofilm formation by crystal violet technique. To evaluate the antiparasitic activity was used to microtiter technique. The results obtained in the determinations of total polyphenols and flavonoids show that the levels of phenolic compounds, in the crude extract was higher, being 97.76 ± 0.65 mg / g for polyphenols and 43.65 ± 1.24 mg / g for flavonoids. The DPPH assay revealed an intermediate capacity reduction for activated free radical, having an IC50 of 86.55 ug / ml for crude extracts. The HPLC analyzes revealed the presence of rosmarinic acid in dichloromethane fraction (7.38 ± 0.08mg / g FS) and cloregênico acid in ethyl acetate fraction (8.4 ± 0.26 mg / g FS). The crude extract and fractions showed antimicrobial activity, being capable of inhibiting growth of E. faecalis ATCC 29212 S. epidermidis ATCC35985, S. saprophyticus ATCC 15305, S. aureus ATCC 33691, S. aureu resistant to methicillin (clinical isolate) L. monocytogenes ATCC 7644, E. coli ATCC 25922, S. enteritidis ATCC 13076, ATCC 12022323A flexineri S., P. aeruginosa ATCC 27853, P. aeruginosa PA01, K. pneumoniae ATCC 1705, at concentrations of 52.4 mg / ml and 3.27 mg / ml. Head Candida species inhibitory concentrations ranged from 52.4 mg / ml to 6.5 mg / ml, and in front Mycobacterium species in the smaller values concentrations able to inhibit growth of the microorganism were between 2.5 mg / ml and 0.625 mg / ml. As regards the reduction of biofilm formation testing the largest percentage of reduction can be seen in dichloromethane fraction, which was the highest concentration able to reduce 83% of the biofilm formation by P. aeruginosa and 51% of C. albicans biofilm formed. To test the antiparasitic, can be observed the decrease of T. evansi 100% after 9h, when exposed to crude extract and N-butanol fraction. This study demonstrates for the first time antiparasitic activity and antibiofilm the crude extract and fractions of rods E.hyemale.